Evaluation of dietary rosemary leaf powder on growth, carcass composition and hemato-biochemical profiles of common carp (Cyprinus carpio) reared in cage system: Rosemary effects on common carp health and growth - S. Omar, Samad (Cellular and Molecular Biology, 2023)
This study was conducted to evaluate the effect of rosemary (Rosmarinus officinalis) leaf powder (RLP) at 0.0% (control), 0.5%, 1% and 2% as a dietary supplement for eight weeks, on the growth performance, carcass composition and haemato-biochemical parameters. One hundred twenty common carp (Cyprinus carpio) (21.11±0.17g) were randomly distributed to 12 cages (0.2 m3) with three replicates for 56 days. The results showed that RLP-supplemented diets achieved significant enhancement of growth performance (FBW, SGR and WG) and feed utilization (FCR, FCE and PI) compared with a control group. In addition, TFI and PI were significantly improved in 0.5 and 2% RLP-supplemented groups. RLP had no significant effects on body composition except moisture content which was significantly increased in fish fed with a 1% supplemented diet and crude protein which was significantly decreased in fish fed with a 1% supplemented diet compared to the control diet. The results showed a significant increase in RLP-supplemented diets in RBC counts, LYM, MCV, hematocrit, total protein, albumin and globulin compared with the control group. WBC counts significantly increased in fish fed the 0.5 and 2% RLP diets, and hemoglobin significantly elevated in fish fed the 1% RLP diet. Glucose, GRA, MCH, MCHC and MPV were significantly decreased in the group fed the RLP diets compared with the control group. The AST, ALT, LDL, VLDL, CHO and TG levels showed a significant decrease in RLP compared to the control diet (P < 0.05), while ALP level fluctuated (P > 0.05). The urea and creatinine levels were higher in the RLP groups compared with the control (P < 0.05). Dietary RLP 1% increased lipase when compared to the control group. However, amylase levels in fish fed 0.5 and 1% RLP has significantly improved, while fish fed 2% RLP has significantly decreased when compared to the control diet. Overall, the results demonstrated that dietary RLP supplementation enhanced the growth and health status of common carp.